Optimalisasi Peran Guru Dalam Mengatasi Bullying Pada Anak Usia Dini di TK Aisyiyah Somoroto Kecamatan Kauman Kabupaten Ponorogo - Yulis Setyaningsih; Dian Kristiana; Muhammad ‘Azam Muttaqin (Jurnal Kajian Anak (J-Sanak), 2023)
The aim of the research is to describe optimizing the role of teachers as transfer of knowledge, motivator and facilitator in overcoming bullying in early childhood. This type of qualitative research is case study. Research objects: teachers and students. Data collection methods are observation, interviews and documentation. The research results show that in order to optimize the role of teachers in the framework of overcoming bullying in early childhood teachers develop role optimization by a). Developing a role as a transfer of knowledge for early childhood through careful planning with varied activities, as well as developing techniques that are considered appropriate to the child's level of development, for example through singing and playing activities. b). Strengthen the role of teachers as motivators to develop student potential, increase student creativity, and arouse students' interest in learning according to their talents, and c). Making the teacher's role effective as a facilitator by seeking learning references, seeking learning resources, and maximizing the use of learning resources to develop learning to be of higher quality.